The disordered N-terminal region of dengue virus capsid protein contains a lipid-droplet-binding motif - Martins, Ivo C. (2012)
©The Authors Journal compilation ©2012 Biochemical Society - 'The final version of record is available at http://www.biochemj.org/bj/